인텔리전스 원천으로서 브랜드 미디어 유형화 연구 - 박상현 (The Graduate School, Ajou University, 2021)
Today’s globalized business environment has made business demands more dynamic and complex than ever. Accordingly, companies have confirmed that customer demands emanate from brand related media, whose importance they have recognized as being important. There are many studies about extracting market needs from brand related media. However, the research focuses on these processes and is limited to specific platforms. Limitations arise when diverse types of brand related media exist, due to processes being limited to a specific platform. Therefore, we categorized these platforms by ‘openness’ and ‘interactivity’ and tested the differences in their underlying market needs information with a quantitative approach. We also proposed "subjectivity", "topic diversity", and "tacit knowledge sharing" to evaluate the characteristics of each brand related media, and set hypotheses based on these. We collected BRM-specific data for the experiment and performed hypothesis testing to derive quantitative results. Part-of-speech tagging, named-entity recognition, and lexicon-based sentiment analysis were applied as methodologies. Finally, we discussed the difference between the four BRM-specific information characteristics and the appropriate BRM utilization method for extracting intelligence from the standpoint of a company.
학위논문(석사)--아주대학교 일반대학원 :인공지능학과,2021. 8
Keywords: brand related media; brand related media typology; media typology; social media; user generated contents